Senhora : profile of a woman - Alencar, José Martiniano de, 1829-1877 (The Texas Pan American series, 1994)
"It is a truth universally acknowledged..." that a single woman in possession of a good character but no fortune must be in want of a wealthy husband - that is, if she is the heroine of a nineteenth-century novel. Senhora, by contrast, turns the tables on this familiar plot. Its strong-willed, independent heroine Aurelia uses newly inherited wealth to "buy back" and exact revenge on the fiance who had left her for a woman with a more enticing dowry.